Aging in urban Japan – intergenerational reading in Tokyo. Issue 1 (2014) - ,
Abstract : Purpose – The purpose of this paper is to introduce a volunteer network from the Tokyo Metropolitan area that addresses the urge for senior citizens to stay mentally active and provide a possibility for them to participate in intergenerational contact as to feel included and useful to society.Design/methodology/approach – The research derives from literature review, local government documents and online presentation as well as an interview that has been conducted by the Tokyo senior information site.Findings – The REPRINTS (Research of Productivity by Intergenerational Sympathy) network in Tokyo is but one answer that combines a mentally challenging activity with intergenerational contact. The network presents an easy to reach and easy to implement diversion for schools to enable children to experience the traditional form of storytelling and help senior citizens to feel challenged and needed.Practical implications – Learning from the experience of the REPRINTS network could help to set up similar activities in other communities that deal with the same problems and are seeking ways to include senior citizens, help them stay active and useful for the community and encourage intergenerational contact.Originality/value – Japan is one of the forerunners when it comes to aging population. Yet, most research still focusses on the challenges, care and especially problems that occur in dying rural areas. This paper instead tries to take a more positive look to the future and concentrates on urban life and its context.